2019
DOI: 10.1016/j.heliyon.2019.e01644
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the prevalence of dyspepsia and practices of dyspepsia management in rural Eastern Uganda

Abstract: Aim To investigate the current prevalence and management of dyspepsia in rural Eastern Uganda. Methods Residents older than 18 years of age across 95 study sites in Namutumba District, Eastern Uganda were surveyed. Each respondent was administered a questionnaire about dyspepsia and pertinent health-seeking behaviors. Health workers at 12 different clinics were also assessed on their competence in managing dyspepsia. Proportion-based analysis was used to determine self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(24 reference statements)
0
7
1
1
Order By: Relevance
“…This study also exhibited dyspeptic symptoms often found among females similar to an existing acquaintance. 17 Cholangitis of variable intensity includes mild, moderate or severe, need fluid and antibiotics administration along with biliary drainage endoscopically followed by cholecystectomy in patients with gallstone accordingly, Ahmed et al, 18 Metastatic disease adopted diverse notions for liver disease, including NAFLD, viral infection, cirrhosis, HCC and/or any combination. Wang et al higher incidence of simultaneous Liver metastasis in patients with HBsAg.…”
Section: Discussionmentioning
confidence: 99%
“…This study also exhibited dyspeptic symptoms often found among females similar to an existing acquaintance. 17 Cholangitis of variable intensity includes mild, moderate or severe, need fluid and antibiotics administration along with biliary drainage endoscopically followed by cholecystectomy in patients with gallstone accordingly, Ahmed et al, 18 Metastatic disease adopted diverse notions for liver disease, including NAFLD, viral infection, cirrhosis, HCC and/or any combination. Wang et al higher incidence of simultaneous Liver metastasis in patients with HBsAg.…”
Section: Discussionmentioning
confidence: 99%
“…Penggunaan obat yang tidak tepat masih sering ditemukan di pusat-pusat kesehatan seperti rumah sakit dan puskesmas. Berdasarkan penelitian Lee et al (2019) menyatakan bahwa lebih dari sepertiga tripel terapi yang diberikan di pusat-pusat kesehatan tidak memadai meliputi durasi pengobatan yang tidak tepat atau dosis yang tidak mencukupi dari satu atau lebih komponen tripel terapi (Lee et al, 2019). Ketidaksesuaian terapi berdasarkan pedoman Formularium Nasional juga terjadi, berdasarkan hasil studi Musnelina dan Dewa (2019) menyatakan bahwa ketidaksesuaian indikasi terapi dispepsia di RS.Tk.IV Cijantung tahun 2016 sebesar 14,1% dengan pemberian jenis terapi berupa omeprazol.…”
Section: Pendahuluanunclassified
“…Dyspepsia, which by definition is the presence of one or more of the symptoms of epigastric pain, bloating, post-prandial fullness, early satiation, and retrosternal pain 1 , is estimated to affect up to 50 % of individuals globally 2 with an estimated higher prevalence in low and middle income countries, particularly Africa with the highest prevalence of uninvestigated dyspepsia 3 . In one community study conducted in rural Uganda, more than 50 % of the respondents reported having had symptoms of dyspepsia 4 . The majority of dyspepsia in Africa is uninvestigated with patients often treated symptomatically.…”
Section: Introductionmentioning
confidence: 99%